Metals exposure dissociates mitochondrial NAD(P)H redox state from H₂O₂ emission - Pius Abraham Tetteh; Zahra Kalvani; Don Stevens; Ravinder Sappal; Collins Kamunde (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Naphthenic acid fraction compounds disrupt bioenergetics, stimulate ROS, and induce necrosis in rainbow trout primary hepatocytes - Zahra Kalvani; Pius A. Tetteh; Collins Kamunde; Don Stevens; Chidozie Okoye; Michael R. van den Heuvel (Aquatic Toxicology, 2026)

Financial analysis & operational assessment of a constructed wetlands system for landfill leachate treatment – A case study - Dreyton J. Lott; Steven Laux; Cassandra Collins; Hannah Sackles; Timothy G. Townsend (Journal of Water Process Engineering, 2026)

Newtonioside, a new cytotoxic cerebroside and other constituents from the stem bark of Newtonia buchananii (Fabaceae) and their chemophenetic significance - Raduis Melong; Steven Collins Njonte Wouamba; Jean Paul Dzoyem; Éric Allémann; Florence Delie; Christian G. Bochet; Gilbert Deccaux Wabo Fotso Kapche (Biochemical Systematics and Ecology, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Nutritional status modulates mitochondrial bioenergetic and redox responses to zinc exposure in rainbow trout - Pius Abraham Tetteh; Zahra Kalvani; Don Stevens; Ravinder Sappal; Collins Kamunde (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A new ceramide and sterols with moderate antibiofilm activity from the underexplored polypore Mushroom Lenzites acuta - Armelle Tontsa Tsamo; Steven Collins Njonté Wouamba; Annette Berole Meli Ngoumfo; Issah Julio Mawouma Pagna; Ibukun Michael Famuyide; Andre Ledoux Njouonkou; Blandine Marlyse Wache Ouahouo; Pierre Mkounga; Jean Paul Dzoyem; Lyndy Joy McGaw; Augustin Ephrem Nkengfack (South African Journal of Botany, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Central American Mangrove Blue Carbon: Distribution, Dynamics and Future Directions - Nicholas T. Girkin; Steven W. J. Canty; Andre S. Rovai; Hannah K. Morrissette; Rachel Collin; Yashvini Shukla; Tania E. Romero-González; Jose Quirós; Jorge Pineda; Jacklyn Rivera Wong; Miguel Cifuentes-Jara (Wetlands, 2026)
Mangroves are one of the most important Blue Carbon ecosystems within the tropics and subtropics, capturing and storing more atmospheric carbon dioxide per unit area than terrestrial forest systems. There is large variation in estimates of carbon stocks of mangroves in Central America, due to differences in underlying geomorphology, localised environmental conditions, and species composition, which also vary between the Pacific and Atlantic coastlines. In this review, we assess our current knowledge of the distribution of mangroves in the region, their role as a carbon sink, our current understanding of their dynamics and resilience, and identify key questions to understand their likely responses to future environmental change processes. This is of particular concern as the Central American region is predicted to experience significant climatic changes, such as increased air and sea surface temperatures, greater frequencies of high intensity cyclones, and increased drought events. Understanding the resilience and vulnerability of these systems will have policy and management implications for the role of Blue Carbon ecosystems as natural climate solutions, ecosystem-based adaptation plans, and disaster risk reduction strategies.

Stereotaxic Delivery of M1000 Prions to the Hippocampus Induces Related Behavioural and Cognitive Changes Consistent with Acute Neurotoxic Effects - Matteo Senesi; Victoria Lewis; Paul A. Adlard; David I. Finkelstein; Jee Hyun Kim; Steven J. Collins (Molecular Neurobiology, 2026)

Unlocking the biofuel power of cover crop in Washington State: Enhancing potential through hydrothermal liquefaction - Daniel Miki Santosa; Teal Potter; Francesca Pierobon; Dilara Göreke; Pimphan Aye Meyer; Chad E. Kruger; Steven Norberg; Douglas Collins; Jonathan Male (Biomass and Bioenergy, 2025)

Ecological risk assessment for Cry1Da_7, Cry1B.3 and Vip3Cb1 proteins expressed in MON 89151 cotton: an insect-protected cotton with targeted activity against Lepidoptera - Harit K. Bal; Collin J. Preftakes; Lawrence Long; Carlos J. Esquivel; Frankie Stubbins; Chitvan Khajuria; Jianguo Tan; David Dyck; Brent Werner; Justin Ungerer; Bingyao Li; Yu Liu-Gontarek; et al. (Transgenic Research, 2025)

Aotearoa New Zealand’s marine carbon cycle in a changing climate – Current understanding and future directions - Scott D. Nodder; Cliff S. Law; Erik Behrens; Sarah J. Bury; Antonia Cristi; Charine Collins; Kim I. Currie; Moira Décima; Alain De Verneil; Pablo C. Escobar‐Flores; Denise Fernandez; Mark P. Gall; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
The marine system plays a critical role in the global climate cycle, as a major control of atmospheric carbon dioxide (CO 2 ). Marine primary production (photosynthesis) and remineralisation of organic carbon (respiration, degradation) determine the amount of CO 2 sequestered in marine sediments and deep‐water environments on century to millennial timescales. The stocks and fluxes of the marine carbon cycle are susceptible to global climate change impacts and other anthropogenic activities that modify key processes. Oceanographic studies of the marine carbon cycle in Aotearoa New Zealand’s Exclusive Economic Zone (NZ EEZ) and Territorial Seas over past decades have provided broad knowledge across a complex and dynamic seascape, but there remain fundamental knowledge gaps that limit identification of and response to present and future anthropogenic threats. In particular, several areas of the EEZ have been under‐sampled and there are currently insufficient data to establish baselines and variability for the marine carbon cycle. We recommend that new observational technologies and ocean modelling applications be fully developed and utilised to enable development of robust predictive capability of our ocean’s response to human‐induced perturbations. Future focus on oceanic nature‐based solutions to accelerate CO 2 uptake will require improved knowledge of the marine carbon cycle in NZ’s EEZ.

Copper, cadmium, and zinc trigger multifaceted effects and interactions on cardiac mitochondrial bioenergetics and reactive oxygen species production in rainbow trout - Pius Abraham Tetteh; Zahra Kalvani; Don Stevens; Ravinder Sappal; Collins Kamunde (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

A “hazard model” using risk-weighted surveillance for first detection of chronic wasting disease - Krysten L. Schuler; Nicholas A. Hollingshead; Steven Heerkens; James D. Kelly; Jeremy E. Hurst; Rachel C. Abbott; Brenda J. Hanley; Eireann Collins; Kevin P. Hynes (Preventive Veterinary Medicine, 2025)

Factors affecting short-term post-release survival probability of Lake Trout implanted with acoustic telemetry transmitters - Alexander J. Gatch; Dimitry Gorsky; Kyle T. Morton; R. Josephine Johnson; Collin J. Farrell; Timothy B. Johnson; Emma J. Bloomfield; Brent Metcalfe; Jessica Goretzke; Michael Connerton; Sarah M. Larocque; Jonathan D. Midwood; et al. (Fisheries Research, 2025)

Using terrain-derived indices and environmental components to examine the spatial context of undocumented immigrant mortality along the USA–MEX border - Justin H. White; Steven M. Radil; Collin S. Philipps; Ian J. Irmischer (Applied Geography, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Interactions of binary mixtures of metals on rainbow trout (Oncorhynchus mykiss) heart mitochondrial H2O2 homeodynamics - Pius Abraham Tetteh; Zahra Kalvani; Don Stevens; Ravinder Sappal; Collins Kamunde (Aquatic Toxicology, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

First records of the sicklefin ( Mobula tarapacana ), bentfin ( Mobula thurstoni ), and spinetail ( Mobula mobular ) devil rays in the Chagos Archipelago - Joanna L. Harris; Claire Collins; Mark Spalding; Guy M. W. Stevens (Journal of Fish Biology, 2024)
Recent encounters with sicklefin ( Mobula tarapacana ) and bentfin ( Mobula thurstoni ) devil rays in the Chagos Archipelago provide the first confirmed observations of live specimens of these species in this region. Examination of illegal fishing photo archives collected during enforcement revealed these endangered species, and spinetail devil rays ( Mobula mobular ), are being caught within the archipelago's vast no‐take marine protected area. Future cooperation between authorities and mobulid ray experts is crucial to improve the availability and accuracy of enforcement data and improve management of illegal fishing and mobulid ray conservation activities.

A model naphthenic acid decouples oxidative phosphorylation through selective inhibition of mitochondrial complex activity - Zahra Kalvani; Collins Kamunde; Don Stevens; Michael R. van den Heuvel (Environmental Toxicology and Pharmacology, 2024)

Remote hideaways: first insights into the population sizes, habitat use and residency of manta rays at aggregation areas in Seychelles - Lauren R. Peel; Mark G. Meekan; Ryan Daly; Clare A. Keating; Shaun P. Collin; Josep Nogués; Guy M. W. Stevens (Marine Biology, 2024)
Understanding the aggregation and habitat use patterns of a species can aid the formulation and improved design of management strategies aiming to conserve vulnerable populations. We used photo-identification techniques and a novel remote underwater camera system to examine the population sizes, patterns of residency and habitat use of oceanic ( Mobula birostris ) and reef ( Mobula alfredi ) manta rays in Seychelles (5.42°S; 53.30°E) between July 2006 and December 2018. Sightings of M. birostris were infrequent ( n = 5), suggesting that if aggregation areas for this species exist, they occur outside of the boundary of our study. A total of 236 individual M. alfredi were identified across all surveys, 66.5% of which were sighted at D’Arros Island (Amirante Group) and 22.5% at St. François Atoll (Alphonse Group). Males and females were evenly represented within the identified population. M. alfredi visited a cleaning station at D’Arros Island less frequently during dawn and dusk than at midday, likely due to the adoption of a crepuscular foraging strategy. The remote and isolated nature of the Amirante and Alphonse Group aggregation areas, coupled with the lack of a targeted mobulid fishery in Seychelles, suggests that with appropriate regulations and monitoring, the marine protected areas gazetted within these two groups will benefit the conservation of M. alfredi in Seychelles.

Comparison of sediment biomarker signatures generated using time-integrated and discrete suspended sediment samples - Hari Ram Upadhayay; Steven J. Granger; Adrian L. Collins (Environmental Science and Pollution Research, 2024)
Sediment source fingerprinting using biomarker properties has led to new insights in our understanding of land use contributions to time-integrated suspended sediment samples at catchment scale. A time-integrated mass-flux sampler (TIMS; also known as the ‘Phillips’ sampler), a cost-effective approach for suspended sediment collection in situ. Such samplers are widely being used to collect sediment samples for source fingerprinting purposes, including studies using biomarkers as opposed to more conventional tracer properties. Here, we assessed the performance of TIMS for collecting representative sediment samples for biomarkers during high discharge events in a small lowland grassland-dominated catchment. Concentrations of long odd-chain n-alkanes (> C 23 ) and both saturated free and bound fatty acids (C 14 -C 32 ), as well as compound-specific 13 C were compared between sediment collected by both TIMS and autosamplers (ISCO). The results showed that concentrations of alkanes, free fatty acids, and bound fatty acids are consistently comparable between TIMS and ISCO suspended sediment samples. Similarly, compound-specific 13 C signals were not found to be significantly different in the suspended sediment samples collected using the different samplers. However, different magnitudes of resemblance in biomarker concentrations and compositions between the samples collected using the two sediment collection methods were confirmed by overlapping index and symmetric coordinates-based correlation analysis. Here, the difference is attributed to the contrasting temporal basis of TIMS (time-integrated) vs. ISCO (discrete) samples, as well as potential differences in the particle sizes collected by these different sediment sampling methods. Nevertheless, our findings suggest that TIMS can be used to generate representative biomarker data for suspended sediment samples collected during high discharge events.

Icequake insights on transient glacier slip mechanics near channelized subglacial drainage - Nathan T. Stevens; Lucas K. Zoet; Dougal D. Hansen; Richard B. Alley; Collin J. Roland; Emily Schwans; Cameron S. Shepherd (Earth and Planetary Science Letters, 2024)

The Nature Smart Cities business model: A rapid decision-support and scenario analysis tool to reveal the multi-benefits of green infrastructure investments - Wito Van Oijstaeijen; Maíra Finizola e Silva; Phil Back; Alexandra Collins; Kris Verheyen; Robbe De Beelde; Jan Cools; Steven Van Passel (Urban Forestry & Urban Greening, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Hydrologic restoration of anthropoentically altered springs in the Sheldon National Wildlife Refuge in the Great Basin, USA - Leah N. Knighton; Steven L. Petersen; Gail H. Collins; Loreen Allphin; Neil C. Hansen; Haley B. Johnston; Russell B. Rader (Journal of Arid Environments, 2023)

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Chemical constituents of two Cameroonian medicinal plants: Sida rhombifolia L. and Sida acuta Burm. f. (Malvaceae) and their antiplasmodial activity - Blaise Cedric Kamdoum; Ingrid Simo; Steven Collins Njonte Wouamba; Brice Mariscal Tchatat Tali; Bathelemy Ngameni; Ghislain Wabo Fotso; Pantaléon Ambassa; Fekam Boyom Fabrice; Bruno Ndjakou Lenta; Norbert Sewald; Bonaventure Tchaleu Ngadjui (Natural Product Research, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Two new triterpenoid fatty acid esters from Schefflera barteri Harms (Araliaceae) § - Judith Flore T. Mbougnia; Gabin Thierry M. Bitchagno; Steven Collins N. Wouamba; Jean-Bosco Jouda; Maurice Ducret Awouafack; Mathieu Tene; Bruno Ndjakou Lenta; Simeon Fogue Kouam; Pierre Tane; Norbert Sewald (Natural Product Research, 2022)

Microbial community structure across grazing treatments and environmental gradients in the Serengeti - Bo Maxwell Stevens; Derek Lee Sonderegger; Nancy Collins Johnson (Soil Ecology Letters, 2022)

Disturbance is complicated: Headward‐eroding saltmarsh creeks produce multiple responses and recovery trajectories - Fengrun Wu; Steven C. Pennings; Collin Ortals; Jennifer Ruiz; W. Reilly Farrell; Samuel M. McNichol; Christine Angelini; Amanda C. Spivak; Merryl Alber; Chunfu Tong (Limnology and Oceanography, 2022)
Disturbances are one of the most important processes affecting natural systems, but there is a gap between simple conceptual models of disturbance and complex empirical studies. We studied the perturbation caused by headward‐eroding creeks in southeastern USA salt marshes. We measured disturbance responses (magnitude and recovery trajectory) of 19 variables. Some variables (shoot density, root biomass, snail density, soil pH, soil strength, soil temperature, elevation) declined sharply, while other variables (crab burrow density, soil organic matter, soil redox) increased sharply, in response to the burrowed and grazed conditions at the creek head. These variables recovered over subsequent years or decades. Other variables (shoot height, aboveground biomass, rhizome biomass, light interception) declined sharply in the creek head, then overshot control values before recovering. Some variables (benthic algae, soil salinity) did not appear to be disturbed by the creek head. As hypothesized, plants recovered before soils and snails. Disturbance magnitude and time to recovery were often greater directly adjacent to the new creekbank than for the same variables in a parallel transect further away from the creekbank, and in some cases variables never converged with control values, indicating a persistent state change. Reducing the dimensionality of the data set into principal component axes obscured the diverse ways in which different aspects of the system responded to and recovered from the perturbation. Our study illustrates the challenges in moving from simple conceptual models of disturbance to empirical studies in which multiple variables are likely to be affected differently and follow different recovery trajectories.

Using an integrative research approach to improve fish migrations in regulated rivers: a case study on Pacific Salmon in the Seton River, Canada - Nolan N. Bett; Scott G. Hinch; Arthur L. Bass; Douglas C. Braun; Nicholas J. Burnett; Matthew T. Casselman; Steven J. Cooke; S. Matthew Drenner; Ahmed Gelchu; William L. Harrower; Roxx Ledoux; Andrew G. Lotto; et al. (Hydrobiologia, 2022)

The Three Glycotypes in the London Classification System of Sporadic Creutzfeldt-Jakob Disease Differ in Disease Duration - Blair Ney; Dhamidhu Eratne; Victoria Lewis; Luke Ney; Qiao-Xin Li; Christiane Stehmann; Steven Collins; Dennis Velakoulis (Molecular Neurobiology, 2021)

Timing and order of different insecticide classes drive control of Drosophila suzukii; a modeling approach - Serhan Mermer; Ferdinand Pfab; Gabriella Tait; Rufus Isaacs; Philip D. Fanning; Steven Van Timmeren; Gregory M. Loeb; Stephen P. Hesler; Ashfaq A. Sial; Jamal H. Hunter; Harit Kaur Bal; Francis Drummond; et al. (Journal of Pest Science, 2021)

Experimental Quantification of Piscivore Density and Habitat Effects on Survival of Juvenile Chinook Salmon in a Tidal Freshwater Estuary - Steven C. Zeug; Michael Beakes; Jesse Wiesenfeld; Marin Greenwood; Lenny Grimaldo; Jason Hassrick; Alison Collins; Shawn Acuña; Myfanwy Johnston (Estuaries and Coasts, 2021)

Holistic Assessment of Biochar and Brown Coal Waste as Organic Amendments in Sustainable Environmental and Agricultural Applications - Collins Amoah-Antwi; Jolanta Kwiatkowska-Malina; Owen Fenton; Ewa Szara; Steven F. Thornton; Grzegorz Malina (Water, Air, & Soil Pollution, 2021)
Organic amendments can improve soil quality which has knock-on environmental and agronomic benefits. However, the use of new and emerging organic amendments such as biochar and brown coal waste (BCW) in soil systems requires continuous holistic assessments for robust consensus building in their environmental and agricultural applications. To examine the application of BCW and woodchip biochar (BIO) in agroecosystems, secondary data from literature on environmental (soil, air and water) aspects were compiled with primary agronomic data from a 3-year multicropping field trial and collated with supplementary data on economic factors (e.g. cost and availability). For the field trial, replicated plots were amended with FYM (for comparative reasons), BCW and BIO at 30, 24.2 and 12.8 for t ha –1 , respectively, with and without NPK and cultivated in a cropping sequence of maize, potato and barley. At the end of each season, soils were characterised for pH, cation exchange capacity (CEC) and fertility (macronutrient contents) in addition to nutrient uptake, nutritional quality and yield of crops. Compared with FYM, biochar and BCW were found to be associated with greater improvements in soil quality (e.g. building of soil structure and C sequestration) and knock-on water and air quality benefits mainly facilitated via increased cation retention and humic-linked sorption which abated gaseous emission and mitigated nutrient and heavy metal leaching. These along with variable improvements in soil chemistry, fertility and nutrient uptake in the agronomic field trial accounted for increased mean crop yield across treatments (higher with NPK): FYM (32.7 and 71.7%), BCW (33.5 and 60.1%) and BIO (21.8 and 48.2%). Additionally, biochar and BCW have lower pollutant (e.g. heavy metals) contents and were found to provide additional sustainability and net abatement cost-benefits. While the agronomic benefits of biochar and BCW were slightly lower compared with that of FYM, their lower environmental footprints and associated sustainability benefits are clear advantages for their adoption in environmental and agricultural applications.

Increasing effects of chronic nutrient enrichment on plant diversity loss and ecosystem productivity over time - Eric W. Seabloom; Peter B. Adler; Juan Alberti; Lori Biederman; Yvonne M. Buckley; Marc W. Cadotte; Scott L. Collins; Laura Dee; Philip A. Fay; Jennifer Firn; Nicole Hagenah; W. Stanley Harpole; et al. (Ecology, 2021)
Human activities are enriching many of Earth’s ecosystems with biologically limiting mineral nutrients such as nitrogen (N) and phosphorus (P). In grasslands, this enrichment generally reduces plant diversity and increases productivity. The widely demonstrated positive effect of diversity on productivity suggests a potential negative feedback, whereby nutrient‐induced declines in diversity reduce the initial gains in productivity arising from nutrient enrichment. In addition, plant productivity and diversity can be inhibited by accumulations of dead biomass, which may be altered by nutrient enrichment. Over longer time frames, nutrient addition may increase soil fertility by increasing soil organic matter and nutrient pools. We examined the effects of 5–11 yr of nutrient addition at 47 grasslands in 12 countries. Nutrient enrichment increased aboveground live biomass and reduced plant diversity at nearly all sites, and these effects became stronger over time. We did not find evidence that nutrient‐induced losses of diversity reduced the positive effects of nutrients on biomass; however, nutrient effects on live biomass increased more slowly at sites where litter was also increasing, regardless of plant diversity. This work suggests that short‐term experiments may underestimate the long‐term nutrient enrichment effects on global grassland ecosystems.

Forest Vegetation Change and Its Impacts on Soil Water Following 47 Years of Managed Wildfire - Jens T. Stevens; Gabrielle F. S. Boisramé; Ekaterina Rakhmatulina; Sally E. Thompson; Brandon M. Collins; Scott L. Stephens (Ecosystems, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Regional Movements of Reef Manta Rays (Mobula alfredi) in Seychelles Waters - Lauren R. Peel; Guy M. W. Stevens; Ryan Daly; Clare A. Keating Daly; Shaun P. Collin; Josep Nogués; Mark G. Meekan (Frontiers in Marine Science, 2020)

Arbuscular mycorrhizal fungi in roots and soil respond differently to biotic and abiotic factors in the Serengeti - Bo Maxwell Stevens; Jeffrey Ryan Propster; Maarja Öpik; Gail W. T. Wilson; Sara Lynne Alloway; Emilian Mayemba; Nancy Collins Johnson (Mycorrhiza, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Marine Vertebrate Biodiversity and Distribution Within the Central California Current Using Environmental DNA (eDNA) Metabarcoding and Ecosystem Surveys - Collin J. Closek; Jarrod A. Santora; Hilary A. Starks; Isaac D. Schroeder; Elizabeth A. Andruszkiewicz; Keith M. Sakuma; Steven J. Bograd; Elliott L. Hazen; John C. Field; Alexandria B. Boehm (Frontiers in Marine Science, 2019)

Ocean Climate Observing Requirements in Support of Climate Research and Climate Information - Detlef Stammer; Annalisa Bracco; Krishna AchutaRao; Lisa Beal; Nathaniel L. Bindoff; Pascale Braconnot; Wenju Cai; Dake Chen; Matthew Collins; Gokhan Danabasoglu; Boris Dewitte; Riccardo Farneti; et al. (Frontiers in Marine Science, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Cerebrospinal Fluid Total Prion Protein in the Spectrum of Prion Diseases - Anna Villar-Piqué; Matthias Schmitz; Ingolf Lachmann; André Karch; Olga Calero; Christiane Stehmann; Shannon Sarros; Anna Ladogana; Anna Poleggi; Isabel Santana; Isidre Ferrer; Eva Mitrova; et al. (Molecular Neurobiology, 2019)

Does fish herding enhance catch rates and detection of invasive bigheaded carp? - Steven E. Butler; Anthony P. Porreca; Scott F. Collins; Jonathan A. Freedman; Joseph J. Parkos; Matthew J. Diana; David H. Wahl (Biological Invasions, 2019)

Spatial heterogeneity in species composition constrains plant community responses to herbivory and fertilisation - Dorothee Hodapp; Elizabeth T. Borer; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Juan Alberti; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Marc Cadotte; Elsa E. Cleland; et al. (Ecology Letters, 2018)
Environmental change can result in substantial shifts in community composition. The associated immigration and extinction events are likely constrained by the spatial distribution of species. Still, studies on environmental change typically quantify biotic responses at single spatial (time series within a single plot) or temporal (spatial beta diversity at single time points) scales, ignoring their potential interdependence. Here, we use data from a global network of grassland experiments to determine how turnover responses to two major forms of environmental change – fertilisation and herbivore loss – are affected by species pool size and spatial compositional heterogeneity. Fertilisation led to higher rates of local extinction, whereas turnover in herbivore exclusion plots was driven by species replacement. Overall, sites with more spatially heterogeneous composition showed significantly higher rates of annual turnover, independent of species pool size and treatment. Taking into account spatial biodiversity aspects will therefore improve our understanding of consequences of global and anthropogenic change on community dynamics.

Estimated Brain Tissue Response Following Impacts Associated With and Without Diagnosed Concussion - Jonathan G. Beckwith; Wei Zhao; Songbai Ji; Amaris G. Ajamil; Richard P. Bolander; Jeffrey J. Chu; Thomas W. McAllister; Joseph J. Crisco; Stefan M. Duma; Steven Rowson; Steven P. Broglio; Kevin M. Guskiewicz; et al. (Annals of Biomedical Engineering, 2018)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Simplified Murine 3D Neuronal Cultures for Investigating Neuronal Activity and Neurodegeneration - Steven J. Collins; Cathryn L. Haigh (Cell Biochemistry and Biophysics, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Heterogeneous changes in avian body size across and within species - Michael D. Collins; George E. Relyea; Erica C. Blustein; Steven M. Badami (Journal of Ornithology, 2017)

Fish introductions and light modulate food web fluxes in tropical streams: a whole‐ecosystem experimental approach - Sarah M. Collins; Steven A. Thomas; Thomas Heatherly; Keeley L. MacNeill; Antoine O. H. C. Leduc; Andrés López‐Sepulcre; Bradley A. Lamphere; Rana W. El‐Sabaawi; David N. Reznick; Catherine M. Pringle; Alexander S. Flecker (Ecology, 2016)
Decades of ecological study have demonstrated the importance of top‐down and bottom‐up controls on food webs, yet few studies within this context have quantified the magnitude of energy and material fluxes at the whole‐ecosystem scale. We examined top‐down and bottom‐up effects on food web fluxes using a field experiment that manipulated the presence of a consumer, the Trinidadian guppy Poecilia reticulata , and the production of basal resources by thinning the riparian forest canopy to increase incident light. To gauge the effects of these reach‐scale manipulations on food web fluxes, we used a nitrogen ( 15 N) stable isotope tracer to compare basal resource treatments (thinned canopy vs. control) and consumer treatments (guppy introduction vs. control). The thinned canopy stream had higher primary production than the natural canopy control, leading to increased N fluxes to invertebrates that feed on benthic biofilms (grazers), fine benthic organic matter (collector‐gatherers), and organic particles suspended in the water column (filter feeders). Stream reaches with guppies also had higher primary productivity and higher N fluxes to grazers and filter feeders. In contrast, N fluxes to collector‐gatherers were reduced in guppy introduction reaches relative to upstream controls. N fluxes to leaf‐shredding invertebrates, predatory invertebrates, and the other fish species present (Hart's killifish, Anablepsoides hartii ) did not differ across light or guppy treatments, suggesting that effects on detritus‐based linkages and upper trophic levels were not as strong. Effect sizes of guppy and canopy treatments on N flux rates were similar for most taxa, though guppy effects were the strongest for filter feeding invertebrates while canopy effects were the strongest for collector‐gatherer invertebrates. Combined, these results extend previous knowledge about top‐down and bottom‐up controls on ecosystems by providing experimental, reach‐scale evidence that both pathways can act simultaneously and have equally strong influence on nutrient fluxes from inorganic pools through primary consumers.

A 2-Substituted 8-Hydroxyquinoline Stimulates Neural Stem Cell Proliferation by Modulating ROS Signalling - Cathryn L. Haigh; Carolin Tumpach; Steven J. Collins; Simon C. Drew (Cell Biochemistry and Biophysics, 2016)

Validation of 14-3-3 Protein as a Marker in Sporadic Creutzfeldt-Jakob Disease Diagnostic - Matthias Schmitz; Elisabeth Ebert; Katharina Stoeck; André Karch; Steven Collins; Miguel Calero; Theodor Sklaviadis; Jean-Louis Laplanche; Ewa Golanska; Ines Baldeiras; Katsuya Satoh; Raquel Sanchez-Valle; et al. (Molecular Neurobiology, 2016)

Stability and Reproducibility Underscore Utility of RT-QuIC for Diagnosis of Creutzfeldt-Jakob Disease - Maria Cramm; Matthias Schmitz; André Karch; Eva Mitrova; Franziska Kuhn; Bjoern Schroeder; Alex Raeber; Daniela Varges; Yong-Sun Kim; Katsuya Satoh; Steven Collins; Inga Zerr (Molecular Neurobiology, 2016)
Real-time quaking-induced conversion (RT-QuIC) allows the amplification of miniscule amounts of scrapie prion protein (PrP Sc ). Recent studies applied the RT-QuIC methodology to cerebrospinal fluid (CSF) for diagnosing human prion diseases. However, to date, there has not been a formal multi-centre assessment of the reproducibility, validity and stability of RT-QuIC in this context, an indispensable step for establishment as a diagnostic test in clinical practice. In the present study, we analysed CSF from 110 prion disease patients and 400 control patients using the RT-QuIC method under various conditions. In addition, “blinded” ring trials between different participating sites were performed to estimate reproducibility. Using the previously established cut-off of 10,000 relative fluorescence units (rfu), we obtained a sensitivity of 85 % and a specificity of 99 %. The multi-centre inter-laboratory reproducibility of RT-QuIC revealed a Fleiss’ kappa value of 0.83 (95 % CI: 0.40–1.00) indicating an almost perfect agreement. Moreover, we investigated the impact of short-term CSF storage at different temperatures, long-term storage, repeated freezing and thawing cycles and the contamination of CSF with blood on the RT-QuIC seeding response. Our data indicated that the PrP Sc seed in CSF is stable to any type of storage condition but sensitive to contaminations with blood (>1250 erythrocytes/μL), which results in a false negative RT-QuIC response. Fresh blood-contaminated samples (3 days) can be rescued by removal of erythrocytes. The present study underlines the reproducibility and high stability of RT-QuIC across various CSF storage conditions with a remarkable sensitivity and specificity, suggesting RT-QuIC as an innovative and robust diagnostic method.

Increased Light Availability Reduces the Importance of Bacterial Carbon in Headwater Stream Food Webs - Sarah M. Collins; Jed P. Sparks; Steven A. Thomas; Sarah A. Wheatley; Alexander S. Flecker (Ecosystems, 2016)

Anthropogenic nitrogen deposition predicts local grassland primary production worldwide - Carly J. Stevens; Eric M. Lind; Yann Hautier; W. Stanley Harpole; Elizabeth T. Borer; Sarah Hobbie; Eric W. Seabloom; Laura Ladwig; Jonathan D. Bakker; Chengjin Chu; Scott Collins; Kendi F. Davies; et al. (Ecology, 2015)
Humans dominate many important Earth system processes including the nitrogen (N) cycle. Atmospheric N deposition affects fundamental processes such as carbon cycling, climate regulation, and biodiversity, and could result in changes to fundamental Earth system processes such as primary production. Both modelling and experimentation have suggested a role for anthropogenically altered N deposition in increasing productivity, nevertheless, current understanding of the relative strength of N deposition with respect to other controls on production such as edaphic conditions and climate is limited. Here we use an international multiscale data set to show that atmospheric N deposition is positively correlated to aboveground net primary production (ANPP) observed at the 1‐m 2 level across a wide range of herbaceous ecosystems. N deposition was a better predictor than climatic drivers and local soil conditions, explaining 16% of observed variation in ANPP globally with an increase of 1 kg N·ha −1 ·yr −1 increasing ANPP by 3%. Soil pH explained 8% of observed variation in ANPP while climatic drivers showed no significant relationship. Our results illustrate that the incorporation of global N deposition patterns in Earth system models are likely to substantially improve estimates of primary production in herbaceous systems. In herbaceous systems across the world, humans appear to be partially driving local ANPP through impacts on the N cycle.

Copper Alters the Effect of Temperature on Mitochondrial Bioenergetics in Rainbow Trout, Oncorhynchus mykiss - Ravinder Sappal; Michelle MacDougald; Don Stevens; Mark D. Fast; Collins Kamunde (Archives of Environmental Contamination and Toxicology, 2014)

Chemistry and Microbial Functional Diversity Differences in Biofuel Crop and Grassland Soils in Multiple Geographies - Lidia S. Watrud; Jay R. Reichman; Michael A. Bollman; Bonnie M. Smith; E. Henry Lee; Julie D. Jastrow; Michael D. Casler; Harold P. Collins; Steven Fransen; Robert B. Mitchell; Vance N. Owens; Brent Bean; et al. (BioEnergy Research, 2013)

The impact of the MJO on clusters of wintertime circulation anomalies over the North American region - Emily E. Riddle; Marshall B. Stoner; Nathaniel C. Johnson; Michelle L. L’Heureux; Dan C. Collins; Steven B. Feldstein (Climate Dynamics, 2013)

Using field-evolved resistance to Cry1F maize in a lepidopteran pest to demonstrate no adverse effects of Cry1F on one of its major predators - Jun-Ce Tian; Hilda L. Collins; Jörg Romeis; Steven E. Naranjo; Richard L. Hellmich; Anthony M. Shelton (Transgenic Research, 2012)

Incorporating clonal growth form clarifies the role of plant height in response to nitrogen addition - Laura Gough; Katherine L. Gross; Elsa E. Cleland; Christopher M. Clark; Scott L. Collins; Joseph E. Fargione; Steven C. Pennings; Katharine N. Suding (Oecologia, 2012)

Microwave Synthesis of Prion Protein Fragments up to 111 Amino Acids in Length Generates Biologically Active Peptides - John A. Karas; Martin Boland; Cathryn Haigh; Vanessa Johanssen; Andrew Hill; Kevin Barnham; Steven Collins; Denis Scanlon (International Journal of Peptide Research and Therapeutics, 2012)

Functional haplotypes of Fc gamma (Fcγ) receptor (FcγRIIA and FcγRIIIB) predict risk to repeated episodes of severe malarial anemia and mortality in Kenyan children - Collins Ouma; Gregory C. Davenport; Steven Garcia; Prakasha Kempaiah; Ateefa Chaudhary; Tom Were; Samuel B. Anyona; Evans Raballah; Stephen N. Konah; James B. Hittner; John M. Vulule; John M. Ong’echa; et al. (Human Genetics, 2012)

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Development and application of GIS datasets for assessing and managing coastal impacts and future change on the central coast of Western Australia - Alexandra Stevens; Lindsay Collins (Journal of Coastal Conservation, 2011)

Legal Liability as Poison Center Consultant - Steven E. Aks; Collin B. Williams; Sean M. Bryant (Journal of Medical Toxicology, 2010)

How Crouch Gait Can Dynamically Induce Stiff-Knee Gait - Marjolein M. van der Krogt; Daan J. J. Bregman; Martijn Wisse; Caroline A. M. Doorenbosch; Jaap Harlaar; Steven H. Collins (Annals of Biomedical Engineering, 2010)

RANK CLOCKS AND PLANT COMMUNITY DYNAMICS - Scott L. Collins; Katharine N. Suding; Elsa E. Cleland; Michael Batty; Steven C. Pennings; Katherine L. Gross; James B. Grace; Laura Gough; Joe E. Fargione; Christopher M. Clark (Ecology, 2008)
Summarizing complex temporal dynamics in communities is difficult to achieve in a way that yields an intuitive picture of change. Rank clocks and rank abundance statistics provide a graphical and analytical framework for displaying and quantifying community dynamics. We used rank clocks, in which the rank order abundance for each species is plotted over time in temporal clockwise direction, to display temporal changes in species abundances and richness. We used mean rank shift and proportional species persistence to quantify changes in community structure in long‐term data sets from fertilized and control plots in a late successional old field, frequently and infrequently burned tallgrass prairie, and Chihuahuan desert grassland and shrubland communities. Rank clocks showed that relatively constant species richness masks considerable temporal dynamics in relative species abundances. In the old field, fertilized plots initially experienced high mean rank shifts that stabilized rapidly below that of unfertilized plots. Rank shifts were higher in infrequently burned vs. annually burned tallgrass prairie and in desert grassland compared to shrubland vegetation. Proportional persistence showed that arid grasslands were more dynamic than mesic grasslands. We conclude that rank clocks and rank abundance statistics provide important insights into community dynamics that are often hidden by traditional univariate approaches.

Shrub encroachment in North American grasslands: shifts in growth form dominance rapidly alters control of ecosystem carbon inputs - ALAN K. KNAPP; JOHN M. BRIGGS; SCOTT L. COLLINS; STEVEN R. ARCHER; M. SYNDONIA BRET‐HARTE; BRENT E. EWERS; DEBRA P. PETERS; DONALD R. YOUNG; GAIUS R. SHAVER; ELISE PENDALL; MEAGAN B. CLEARY (Global Change Biology, 2008)
Shrub encroachment into grass‐dominated biomes is occurring globally due to a variety of anthropogenic activities, but the consequences for carbon (C) inputs, storage and cycling remain unclear. We studied eight North American graminoid‐dominated ecosystems invaded by shrubs, from arctic tundra to Atlantic coastal dunes, to quantify patterns and controls of C inputs via aboveground net primary production (ANPP). Across a fourfold range in mean annual precipitation (MAP), a key regulator of ecosystem C input at the continental scale, shrub invasion decreased ANPP in xeric sites, but dramatically increased ANPP (>1000 g m −2 ) at high MAP, where shrub patches maintained extraordinarily high leaf area. Concurrently, the relationship between MAP and ANPP shifted from being nonlinear in grasslands to linear in shrublands. Thus, relatively abrupt (

Fine mapping and targeted SNP survey using rice-wheat gene colinearity in the region of the Bo1 boron toxicity tolerance locus of bread wheat - Thorsten Schnurbusch; Nicholas C. Collins; Russell F. Eastwood; Tim Sutton; Steven P. Jefferies; Peter Langridge (Theoretical and Applied Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Environmental and plant community determinants of species loss following nitrogen enrichment - Chris M. Clark; Elsa E. Cleland; Scott L. Collins; Joseph E. Fargione; Laura Gough; Katherine L. Gross; Steven C. Pennings; Katherine N. Suding; James B. Grace (Ecology Letters, 2007)
Global energy use and food production have increased nitrogen inputs to ecosystems worldwide, impacting plant community diversity, composition, and function. Previous studies show considerable variation across terrestrial herbaceous ecosystems in the magnitude of species loss following nitrogen (N) enrichment. What controls this variation remains unknown. We present results from 23 N‐addition experiments across North America, representing a range of climatic, soil and plant community properties, to determine conditions that lead to greater diversity decline. Species loss in these communities ranged from 0 to 65% of control richness. Using hierarchical structural equation modelling, we found greater species loss in communities with a lower soil cation exchange capacity, colder regional temperature, and larger production increase following N addition, independent of initial species richness, plant productivity, and the relative abundance of most plant functional groups. Our results indicate sensitivity to N addition is co‐determined by environmental conditions and production responsiveness, which overwhelm the effects of initial community structure and composition.

Mapping diabetes QTL in an intercross derived from a congenic strain of the Brown Norway and Goto-Kakizaki rats - Stephan C. Collins; Robert H. Wallis; Steven P. Wilder; Karin J. Wallace; Karène Argoud; Pamela J. Kaisaki; Marie-Thérèse Bihoreau; Dominique Gauguier (Mammalian Genome, 2006)

Genetic prion disease: the EUROCJD experience - Gábor G. Kovács; Maria Puopolo; Anna Ladogana; Maurizio Pocchiari; Herbert Budka; Cornelia van Duijn; Steven J. Collins; Alison Boyd; Antonio Giulivi; Mike Coulthart; Nicole Delasnerie-Laupretre; Jean Philippe Brandel; et al. (Human Genetics, 2005)

Integration of soil solarization with chemical, biological and cultural control for the management of soilborne diseases of vegetables - C. Stevens; V. A. Khan; R. Rodriguez-Kabana; L. D. Ploper; P. A. Backman; D. J. Collins; J. E. Brown; M. A. Wilson; E. C. K. Igwegbe (Plant and Soil, 2003)

The synthesis and spectroscopic analysis of the neurotoxic prion peptide 106–126: Comparative use of manual Boc and Fmoc chemistry - Michael F. Jobling; Colin J. Barrow; Anthony R. White; Colin L. Masters; Steven J. Collins; Roberto Cappai (International Journal of Peptide Research and Therapeutics, 1999)

Extreme resistance to infection by potato virus Y and potato virus X in an advanced hybridSolanum phureja — S. Stenotomum diploid potato population - Roger L. Vallejo; Wanda W. Collins; Rocco D. Schiavone; Steven A. Lommel; J. B. Young (American Journal of Potato Research, 1994)